2012
DOI: 10.1155/2012/727810
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation with fMRI of Patients with Intracranial Gliomas

Abstract: Introduction. Aggressive surgical resection constitutes the optimal treatment for intracranial gliomas. However, the proximity of a tumor to eloquent areas requires exact knowledge of its anatomic relationships to functional cortex. The purpose of our study was to evaluate fMRI's accuracy by comparing it to intraoperative cortical stimulation (DCS) mapping. Material and Methods. Eighty-seven patients, with presumed glioma diagnosis, underwent preoperative fMRI and intraoperative DCS for cortical mapping during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 64 publications
3
28
0
2
Order By: Relevance
“…Nevertheless, fMRI has been widely implemented for presurgical mapping of both sensorimotor and language areas. Studies comparing fMRI and ICS maps in visual cortex have also reported good correspondence 27,28 . Yet for a variety of reasons, fMRI vision mapping has not been used as widely in the clinic despite its potential utility (see DeYoe et al, 2011 21 ).…”
Section: Clinical Applicationmentioning
confidence: 86%
“…Nevertheless, fMRI has been widely implemented for presurgical mapping of both sensorimotor and language areas. Studies comparing fMRI and ICS maps in visual cortex have also reported good correspondence 27,28 . Yet for a variety of reasons, fMRI vision mapping has not been used as widely in the clinic despite its potential utility (see DeYoe et al, 2011 21 ).…”
Section: Clinical Applicationmentioning
confidence: 86%
“…However the correspondence between the two techniques is often reported qualitatively and finding metrics to address this quantitatively has been challenging (Vlieger et al, 2004). One approach is to measure the distance between the center of fMRI and ECS localizations (Kapsalakis et al, 2012), however the extent is likely as important as the center when the goal is to avoid postoperative deficits. Other studies have reported the number of ECS points that fall within the activated area of fMRI, however this is critically dependent on the threshold used to differentiate “activated” from “non-activated” voxels and the spatial locations of ECS-negative points are often not recorded (Vlieger et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Now that our technique is validated with motor mapping, there is good motivation to begin testing it for language and memory. Pre-operative fMRI mapping of these functions tends to be less robust than motor mapping and thus there is greater need for improvement (Hirsch et al, 2000; Kapsalakis et al, 2012; Mehta and Klein, 2010). Further, there is good reason to think our algorithm will prove useful in these other domains.…”
Section: Discussionmentioning
confidence: 99%
“…They may not be fully reliable and they need future refinement for improved accuracy. While fMRI is helpful in surgical planning (Kapsalakis et al, 2012) and it may predict outcome on a group level after anterior temporal lobectomy, we do not know the optimal set of fMRI memory paradigms, in particular, for cases in who there may be atypical memory dominance or in who there may be a dissociation between memory and language. Thus, Wada test is still necessary to identify rare cases with atypical dominance of cognitive functions.…”
Section: Discussionmentioning
confidence: 99%